2019
DOI: 10.1515/bot-2018-0119
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and temperature adaptability of cultivable fungi in marine sediments from the Chukchi Sea

Abstract: In recent years, the Arctic has become a hot spot for microbial research. However, fungal diversity in the Chukchi Sea (adjacent to the Arctic Ocean) is little known. The purpose of this study was to explore fungal diversity in sediments of the Chukchi Sea and the temperature adaptability of the cultured fungi. A total of 74 fungal strains were isolated from nine marine sediment samples collected from the Chukchi Sea. These fungi were identified based on morphological characteristics and sequence comparison of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
0
9
0
3
Order By: Relevance
“…Fungi remain one of the most understudied group of microbial organisms in the ocean and they represent a good source for novel biochemistry (Liberra and Lindequist 1995 ; Richards et al 2011 ; Berlinck 2013 ; Wang et al 2015 ). The relatively few studies on cultivable fungi undertaken in the Arctic underlines the importance of mapping and exploring the species richness and capabilities of marine fungi in this region (Rämä et al 2017 ; Luo et al 2019 ). The present study provides the first insight into the bioactivity of cultivable marine fungi isolated from diverse substrates from cold waters of the Arctic region.…”
Section: Discussionmentioning
confidence: 99%
“…Fungi remain one of the most understudied group of microbial organisms in the ocean and they represent a good source for novel biochemistry (Liberra and Lindequist 1995 ; Richards et al 2011 ; Berlinck 2013 ; Wang et al 2015 ). The relatively few studies on cultivable fungi undertaken in the Arctic underlines the importance of mapping and exploring the species richness and capabilities of marine fungi in this region (Rämä et al 2017 ; Luo et al 2019 ). The present study provides the first insight into the bioactivity of cultivable marine fungi isolated from diverse substrates from cold waters of the Arctic region.…”
Section: Discussionmentioning
confidence: 99%
“…Hyphae were visibly protruding from the inside of carcasses, definitively proving the endobiotic nature of these fungi. Penicillium species are globally distributed (Hassett et al 2019b), produce a suite of degradative enzymes (Park et al 2019), are commonly found in seafood (Park et al 2019), and can be abundant in the Arctic (Luo et al 2020). Our mortality experiments indicate that the presence of select P. chrysogenum strains can differentially reduce survival in copepods during a time span of weeks, consistent with variable virulence among strains of the same fungal species (Kowalski and Cramer 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Но в последние 20 лет ситуация стала меняться, появляется все больше исследований микобиоты этих местообитаний. Основное внимание пока сосредоточено на исследовании разнообразия грибов в донных грунтах различных широт [3][4][5][6] и глубин [7][8][9][10], а также на изучении отдельных особенностей выделенных культур [11,12]. Этими работами продемонстрировано, что морские грунты -местообитание, богатое грибами, а их видовое разнообразие зачастую очень высоко.…”
Section: ключевые слова: морские грибы Ascomycota донные грунты раunclassified
“…Этими работами продемонстрировано, что морские грунты -местообитание, богатое грибами, а их видовое разнообразие зачастую очень высоко. Это относится как к прибрежным [3,[8][9][10][11], так и к удаленным от берега [4,7,12] районам. В настоящее время исследования разнообразия грибов в донных осадках мирового океана и их приспособлений к условиям среды -актуальные направления морской микологии [11,12].…”
Section: ключевые слова: морские грибы Ascomycota донные грунты раunclassified
See 1 more Smart Citation